The impact of minimum wage on the spatial distribution of exporting hazard rate: The empirical research using the data from the annual survey of Chinese industrial firms over the period 1998-2007 - Ruili Zhao; Churen Sun; Tao Zhang (European Regional Science Association (ERSA), 2013)
As cities play important roles in economic growth, the competitive power of foreign trade of cities has gained more and more attentions. Exporting hazard rate, as one dimension of foreign competitive power, shall be specifically measured. And its spatial distribution across cities shall be analyzed. However, few literatures investigates spatial distribution of export hazard rate. This paper estimates firm-level export hazard rates using the Cloglog model based on the data from the Annual Survey of Industrial Enterprises in China, and then aggregate them to city-level. We then analyze the impact of different factors on city-level export hazard rate using the spatial econometrical method. Empirical results show that minimum wage and agglomeration economy spatially affect city-level export hazard rate. Minimum wage significantly increases while agglomeration economy reduces a citys export harzard rate. However, the spatial relevance of minimum wage and agglomeration economy across space has accordingly significantly contrary impacts. These results imply apparently the existence of the count-competition system in China.
Keywords: 330; Export hazard rate; spatial distribution; agglomeration; minimum wage